Comparative efficacy of combination fansidar-sulphate-quinine and fansidar-cbloroquine in mixed malaria infections of P. falciparum - P. vivax in children - A. Liando; T. H. Rampengan (Paediatrica Indonesiana, 1991)
From January 1987 until March 1990, 61 children suffering from mixed malaria infections of P. falciparum and P. vivax entered the Department of Child Health Medical School Sam Ratulangi University/Gunung Wenang General Hospital, Manado. Only 41 patients were evaluated as 20 patients did not fulfill the inclusion criteria. Twenty patients were treated with fansidar-quinine (Group I), and 21 patients with fansidar chloroquine (Group II). In group II, the asexual form of P. vivax disappeared in 2 days after having been treated with fansidar-chloroquine. Conversely, in group I the asexual form of P. vivax disappeared after 5 days o[ treatment. Statistical analysis showed a significant difference (p<0.001). No significant difference .could be detected between the duration of asexual parasitemia of P. falciparum in these two groups (p=0.3085). No statistically significant difference could be detected concerning the duration of fever and the length of hospitalization between these rwo groups.